Impacts of the unsaturation degree of long-chain fatty acids on the volatile fatty acid profiles of rumen microbial fermentation in goats in vitro - Jian GAO; Meng-zhi WANG; Yu-jia JING; Xue-zhao SUN; Tian-yi WU; Liang-feng SHI (Journal of Integrative Agriculture, 2016)
This study investigated the impacts of the degree of unsaturation (unsaturity) of long-chain fatty acids on volatile fatty acid (VFA) profiles of rumen fermentation in vitro. Six types of long-chain fatty acids, including stearic acid (C18:0, control group), oleic acid (C18:1, n-9), linoleic acid (C18:2, n-6), α-linolenic acid (C18:3, n-3), arachidonic acid (C20:4, n-6) and eicosapentaenoic acid (C20:5, n-3), were tested. Rumen fluid from three goats fitted with ruminal fistulae was used as inoculum and the inclusion rate of long-chain fatty acid was at 3% (w/w) of substrate. Samples were taken for VFA analysis at 0, 3, 6, 9, 12, 18 and 24 h of incubation, respectively. The analysis showed that there were significant differences in the total VFA among treatments, sampling time points, and treatment×time point interactions (P<0.01). α-Linolenic acid had the highest total VFA (P<0.01) among different long-chain fatty acids tested. The molar proportion of acetate in total VFA significantly differed among treatments (P<0.01) and sampling time points (P<0.01), but not treatment×time point interactions (P>0.05). In contrast, the molar proportion of propionate did not differ among treatments during the whole incubation (P>0.05). However, for butyrate molar proportions, significant differences were found not only among sampling time points but also among treatments and treatment×time point interactions (P<0.01), with eicosapentaenoic acid having the highest value (P<0.01). Additionally, no statistically significant differences were found in the acetate to propionate ratios among treatments groups (P>0.05), even the treatments stearic acid and α-linolenic acid were numerically higher than the others. The inclusion of 3% long-chain unsaturated fatty acids differing in the degree of unsaturation brought out a significant quadratic regression relation between the total VFA concentration and the double bond number of fatty acid. In conclusion, the α-linolenic acid with 3 double bonds appeared better for improving rumen microbial fermentation and the total VFA concentration.